Frequency of Smoking and Smokeless Tobacco and Its Impact on In Hospital Outcomes of Patient Less Than 45 Years of Age with ACS - Khan, Sumaira Fareed; Urooj, Abiha; Younis, Muhammad; Ali, Saher; Kainat; Khumar, Rajesh (Indus Journal of Bioscience Research, 2025)
Objective: This study has been designed to determine frequency of smoking and smokeless tobacco and its impact on in-hospital MACE among acute coronary syndrome patients of age less than 45 years managed at public sector hospital in Karachi, Pakistan. Methodology: This cross-sectional study was performed in Department of Cardiology, National Institute of Cardiovascular Diseases, Karachi from 1st January 2024 to 30th July 2024. Patients of both the gender of age at least 18-45 years and presenting with ACS were studied. Patients were followed till their discharge or in-hospital mortality to record final outcome. Results: Total 172 patients were studied with mean age of 40.5 ± 4.8 years. Majority of participants were males (89%). Most of the patients were smokers (39.5%) while some were consuming smokeless tobacco (12.2%) and few were using both (3.5%). Smoking was higher in males (100% versus 0%) whereas smokeless tobacco consumption was higher in females (38.1% versus 61.9%). Among smokers, STEMI (60.3%) was more prevalent followed by nSTEMI (23.5%) and unstable angina (16.2%). In smokeless tobacco users, unstable angina (61.9%) was more common followed by nSTEMI (28.6%) and STEMI (9.5%). Multiple level disease was more common in smokers (66.2%) while among smokeless tobacco users single level was common (66.7%). Education and comorbidity was significantly different. Conclusion: The present study found that STEMI and multi-level vessel disease was common in smokers whereas in consumers of smokeless tobacco, unstable angina and single-level disease was frequent. No differences were found in terms of mortality among smokers, consumers of smokeless tobacco and those who were not smoking.